Ethnopharmacological Approaches for Therapy of Jaundice: Part I - Tewari, Devesh; Mocan, Andrei; Parvanov, Emil D.; Sah, Archana N.; Nabavi, Seyed M.; Huminiecki, Lukasz; Ma, Zheng Feei; Lee, Yeong Yeh; Horbańczuk, Jarosław O.; Atanasov, Atanas G. (Frontiers in Pharmacology, 2017)
Jaundice is a very common symptom especially in the developing countries. It is associated with several hepatic diseases which are still major causes of death. There are many different approaches to jaundice treatment and the growing number of ethnomedicinal studies shows the plant pharmacology as very promising direction. Many medicinal plants are used for the treatment of jaundice, however a comprehensive review on this subject has not been published. The use of medicinal plants in drug discovery is highly emphasized (based on their traditional and safe uses in different folk medicine systems from ancient times). Many sophisticated analytical techniques are emerging in the pharmaceutical field to validate and discover new biologically active chemical entities derived from plants. Here, we aim to classify and categorize medicinal plants relevant for the treatment of jaundice according to their origin, geographical location and usage. Our search included various databases like Pubmed, ScienceDirect, Google Scholar. Keywords and phrases used for these searches included: “jaundice”, “hyperbilirubinemia”, “serum glutamate”, “bilirubin”, “Ayurveda”. The first part of the review focuses on the variety of medicinal plant used for the treatment of jaundice (a total of 207 medicinal plants). In the second part, possible mechanisms of action of biologically active secondary metabolites of plants from five families for jaundice treatment are discussed.